Empowerment of whom? The gap between what the system provides and patient needs in hip fracture management: A healthcare professionals' lifeworld perspective. (August 2020) - Jensen, Charlotte M.; Santy-Tomlinson, Julie; Overgaard, Soeren; Wiil, Uffe Kock; Jakobsen, Pernille Ravn; Smith, Anthony C.; Clemensen, Jane
Abstract: Aims and objectives: To use a Habermasian lifeworld theoretical perspective to illuminate a treatment gap for hip fracture patients in a Danish university hospital to guide future healthcare services. Background: Most healthcare systems focus on systematised guidelines to help reduce hospital length of stay in response to increasing demand because of the ageing of the global population. For patients with hip fractures, a previous study demonstrated that there is a lack of patient empowerment and a gap between patients' needs and wishes and what was provided by the healthcare system. Design: In this follow-up study, the previous findings were introduced to a mixed group of health professionals (HPs) who participated in focus group discussions (n = 3, with a total of 18 HPs). Methods: Data were analysed using qualitative content analysis. By analysing the discourse of the discussions using Habermas' perspective, the lack of patient-empowerment was illuminated and facilitated, describing it in terms of the gap it creates in communicative actions between HPs and patients. Results: Information and education of patients in systematised pathways, such as those for patients with hip fractures, are dominated by a biomedical discourse. Patients are overwhelmed by the psycho-social implications of the hip fracture, leaving them in a shock-like state of mind. Conclusion: Empowerment of patients should involve empowerment of HPs by providing them with skills to support patients in a shock-like state of mind. There is also a need to provide HPs with a more individually targeted means of informing and educating patients.